The role of vitamin A in reducing child mortality and morbidity and improving growth - RAMAKRISHNAN USHA; MARTORELL REYNALDO (Instituto Nacional de Salud Pública, 1998)
This is an update of knowledge on the role of the vitamin A status in determining child mortality, morbidity and growth. Recent information confirms the earlier conclusion of Beaton et al. that a 23% reduction in young child mortality results following improvements in the vitamin A status. Studies show that the mortality effect is primarily due to reductions in deaths due to acute gastroenteritis and measles but not acute respiratory infections (ARI) and malaria. While improvement of the vitamin A status enhances the survival of older preschool children, it remains unclear whether it benefits infants (i.e. <6 months). Vitamin A supplementation does not reduce the overall incidence and prevalence of common childhood illness; however, it reduces the incidence of more severe episodes of diarrhea. Also, vitamin A supplementation either during and/or immediately after the illness does not improve its symptomatology. Finally, contrary to earlier expectations, recently completed, placebo-controlled randomized interventions have failed to detect improvements in child growth.